Impact of capital structure on firm performance : evidence from Malaysia plantation firms - Yong, Hooi Ying (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The objective of the study is to examine the impact of the capital structure of firm performance in Malaysia. The investigation has been performed using panel data procedure for a sample of 10 Malaysian listed plantation firms on the Bursa Malaysia Stock exchange during 2008-2014 .. The data is focusing in one sector which is plantation sector. The study is conducted with two performance measures which are included Return on Equity (ROE) and Return on Assets (ROA) as dependent variables. There have three capital structure measures which included Short Term Debt (STD), Long Term Debt (LTD) and Total Debt (TID) as independent variable in this study The results indicate that firm performance, which is measured by Return on Asset (ROA) and Return on Equity (ROE). Both dependent variables have a significant positive relationship with Short Term Debt (STD) and Long Term Debt (LTD), but having significant negative relationship with Total Debt (TID) throughout ofthis study.